Molecular cloning and characterization of genes encoding chitinase and N-acetyl-Î²-glucosaminidase in Dolerocypris sinensis - Cheng, Gong; Li, Shaonan (Cellular and Molecular Biology, 2019)
Chitinases and N-acetyl-Î²-glucosaminidase (NAG) are important in molting and growth of crustaceans. In ostracods, the genes encoding these enzymes have not been characterized. The aim of the present study was to clone the genes encoding chitinase (DsChi) and NAG (DsNAG) from the ostracod, Dolerocypris sinensis, elucidate the phylogenetic relationships between the cloned genes and known chitinolytic enzymes, and determine the expression patterns of these genes at different stages of growth in the presence of an environmental pollutant. The genes were amplified from the genomic DNA of the organism using polymerase chain reaction (PCR). The products from PCR were cloned and characterized with bioinformatics tools, and their expression patterns at different growth stages were determined using real-time quantitative PCR (qRT-PCR). Nine and five introns were identified in DsChi and DsNAG genes, respectively. When compared with protein sequences available in GenBank, chitinase from D. sinensis was most closely related to that of Macrobrachium nipponense (61 % homology). The NAG of D. sinensis was most closely related to that of Limulus polyphemus (55.6 % homology). Based on phylogenetic analysis of known chitinases from crustaceans and insects, the D. sinensis chitinase tightly clustered in the same branch with chitinases from species within the Malacostraca class. In contrast, NAG of D. sinensis was clustered with NAG from F. candida.The level of expression of DsChi mRNA was significantly higher than that of DsNAG throughout the period of growth (p < 0.05). Treatment of D. sinensis cells with fenoxycarb significantly downregulated the expressions of DsChi and DsNAG throughout the period of growth (p < 0.05). These results show that the protein products of DsChi and DsNAG possess remarkable biochemical properties characteristic of a chitinase and NAG, respectively.